Catalyst‐Controlled Switch in Chemo‐ and Diastereoselectivities: Annulations of Morita–Baylis–Hillman Carbonates from Isatins. (6th January 2016) - Zhan, Gu; Shi, Ming‐Lin; He, Qing; Lin, Wei‐Jia; Ouyang, Qin; Du, Wei; Chen, Ying‐Chun
Abstract: Regulating both the chemo‐ and diastereoselectivity, divergently, of a reaction is highly attractive but extremely challenging. Presented herein is a catalyst‐controlled switch in the chemo‐ and diastereodivergent annulation reactions of Morita–Baylis–Hillman carbonates, derived from isatins and 2‐alkylidene‐1 H ‐indene‐1, 3(2 H )‐diones, in exclusive α‐regioselectivity. α‐Isocupreine efficiently catalyzed [2+1] reactions to access cyclopropane derivatives, and the diastereodivergent [3+2] annulations were accomplished by employing either a chiral phosphine or a DMAP‐type molecule. All reactions exhibited excellent chemoselectivities, and good to remarkable stereoselectivities were furnished, thus leading to a collection of compounds with skeletal and stereogenic diversity. Moreover, DFT computational calculations elucidated the catalyst‐based switch in mechanism.